A non-contact remote digital dermoscope to support cancer screening and diagnosis of inflammatory skin disease. (13th September 2017) - Meinhardt-Wollweber, Merve; Heratizadeh, Annice; Basu, Chandrajit; Günther, Axel; Schlangen, Sebastian; Werfel, Thomas; Schacht, Vivien; Emmert, Steffen; Haenssle, Holger A; Roth, Bernhard
Abstract: Dermoscopy systems that do not require direct skin contact open up the possibility to overcome limitations of established dermoscopes and promote application of this diagnostic tool beyond skin cancer screening. In this work, we present a non-contact remote digital dermoscope with large field of view, high resolution and true color imaging. We report preliminary clinical results for imaging of melanocytic nevi and two common inflammatory skin diseases, psoriasis and lichen ruber planus, obtained in non-contact mode demonstrating the potential of this method for skin cancer screening and for diagnosis of inflammatory disease. In the future, the system can be applied for whole-body automated cancer screening and support diagnostics of inflammatory skin diseases in the form of a hand-held device.